2005
DOI: 10.1007/s00109-005-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated xylosyltransferase I activities in pseudoxanthoma elasticum (PXE) patients as a marker of stimulated proteoglycan biosynthesis

Abstract: Pseudoxanthoma elasticum (PXE) is a hereditary disorder of the connective tissue characterized by extracellular matrix alterations with elastin fragmentation and excessive proteoglycan deposition. Xylosyltransferase I (XT-I, E.C. 2.4.2.26) is the initial enzyme in the biosynthesis of the glycosaminoglycan chains in proteoglycans and has been shown to be a marker of tissue remodeling processes. Here, we investigated for the first time serum XT-I activities in a large cohort of German PXE patients and their unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…We determined the occurrence of the c.3421CϾT mutation in PXE patients and their relatives as we have described previously (13,32 ). We found 11 (10%) homozygous and 40 (36.4%) heterozygous carriers of the common c.3421CϾT mutation in the patient group, whereas 13 (24.5%) relatives were heterozygous for this mutation.…”
Section: Abcc6 Genotypingmentioning
confidence: 86%
See 1 more Smart Citation
“…We determined the occurrence of the c.3421CϾT mutation in PXE patients and their relatives as we have described previously (13,32 ). We found 11 (10%) homozygous and 40 (36.4%) heterozygous carriers of the common c.3421CϾT mutation in the patient group, whereas 13 (24.5%) relatives were heterozygous for this mutation.…”
Section: Abcc6 Genotypingmentioning
confidence: 86%
“…Further investigations revealed enhanced elastin degradation leading to high amounts of demosines in the urine and plasma of PXE patients (31 ). We recently found increased xylosyltransferase I activity in the sera of PXE patients, which reflects the extracellular matrix alterations (32 ). Despite these findings, the implication of MRP6 in calcium-phosphate metabolism remains unknown.…”
mentioning
confidence: 99%
“…Using a limited haplotype analysis with the microsatellite markers D16B9621 and D16S764, the five intragenic SNPs c.1841T>C, c.2490C>T, c.3803G>A, c.4404-76A>G and c.4404-31G>A and the intragenic mutation c.3421C>T, a deletion of the whole ABCC6 gene could be excluded in homozygous state in all patients and in heterozygous state in all but 2 PXE patients. Saux et al, 2001;B, Miksch et al, 2005;C, Cai et al, 2001;D, Chassaing et al, 2004;E, Meloni et al, 2001;F, Hendig et al, 2004;G, Schulz et al, 2005a;H, Hu et al, 2003;I, Uitto et al, 2001;J, Le Saux et al, 2000;K, Gheduzzi et al, 2004;L, Schulz et al, 2005b;M, Götting et al, 2004;N, Ringpfeil et al, 2000;O, Bergen et al, 2000;P, Struk et al, 2000;Q, Pulkkinen et al, 2001;R, Ringpfeil et al, 2001;S, Götting et al, 2005. F = female, M = male, wt = wild-type, hm = homozygote, ht = heterozygote, cht = compound heterozygote, nd = not determined, MSM = microsatellite marker, E = eyes, S = skin, G = gastrointestinum, H = heart, V = vascular tissue and A = arterial hypertension. a The PXE families are consecutively numbered and the affected family members are indicated by following numbers.…”
Section: Pxe Mutations Discovered By Dhplc Analysismentioning
confidence: 99%
“…12,13 Indeed, several studies reported alterations in systemic blood components in PXE patients and mouse models due to MRP6 deficiency. [14][15][16][17][18][19][20] Accordingly, PXE was assumed to be primarily a metabolic disorder. 12,[21][22][23] In contrast, results of several studies also point to a local role for ABCC6/MRP6 as expression of the protein was detected in dermal fibroblasts from healthy controls whereas it was found to be absent in fibroblasts from PXE patients.…”
mentioning
confidence: 99%